AKTIVITAS ANTIBAKTERI LOTION MINYAK KAYU MANIS TERHADAP Staphylococcus epidermidis PENYEBAB BAU KAKI - Fitri Apriliyani Tiran; Christofori M.R.R. Nastiti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Trans-cinnamaldehyde is the major chemical compound of cinnamon oil which is potential as anantibacterial agent. Due to this activity, Cinnamon oil can be formulated into a lotion for practical use.This study aimed to determine the antibacterial activity of cinnamon oil and cinnamon oil lotion againstStaphylococcus epidermidis, which causes unacceptable foot odor. This study was a pure experimentalstudy. Stages of this study were starting from the obsevation of antibacterial activity of Cinnamon oilagainst Staphylococcus epidermidis which was done by using diffusion method to determine theconcentrations used in the formulation. Cinnamon oil was then formulated into lotions with variation ofconcentrations of 12; 18; and 24% (w/w) respectively. Furthermore, the quality of lotion based on itsphysical properties such as viscosity and spread-ability, and the antibacterial activity of lotion weredetermined. The inhibition zones then were statistically analyzed by using the Kruskal-Wallis test withassistance of R 2.14.1software. The result showed that cinnamon oil lotion had good physical properties ata concentration of 12% (w/w). Cinnamon oil itself and the formulations had significant activity againstStaphylococcus epidermidis. Moreover, cinnamon oil and its formulation showed similar antibacterialactivity against Staphylococcus epidermidis.Keywords : antibacterial activity, cinnamon oil, lotion, Staphylococcus epidermidis